(untitled) (The Review of Diabetic Studies, 2023)
The nonobese diabetic (NOD) mouse has provided an important animal model for studying the mechanism and genetics of type 1 diabetes over the past 30 years. Arguably, the bio-breeding (BB) rat model may be an even closer phenotypic mimic of the typical human disease. A large number of distinct genetic traits which influence diabetes development have been defined through an extraordinary effort, most conspicuously in the mouse model. However, in both NOD and BB models the lack of availability of robust means for experimental genetic manipulation has restricted our understanding of the mechanisms underlying this spontaneous autoimmune disease. Recent developments in the derivation of embryonic stem (ES) cells have the potential to transform this picture. We argue here that targeting of NOD strain ES cells can bring much needed certainty to our present understanding of the genetics of type 1 diabetes in the NOD mouse. In addition, ES cells can play important roles in the future, in both the NOD mouse and BB rat models, through the generation of new tools to investigate the mechanisms by which genetic variation acts to promote diabetes.